New Ecological Observations and Occurrence for Asteroidea and Echinoidea in Hong Kong - Yiu, Sam King Fung; Mah, Christopher L. (Zootaxa, 2024)
This paper reports several new occurrences for Asteroidea and Echinoidea in Hong Kong. New records for asteroids include Anseropoda rosacea, Aquilonastra cepheus, Pentaceraster alveolatus, Pentaceraster sibogae, and Culcita novaeguineae. For echinoids, new records include Coelopleurus maculatus, Eucidaris metularia, Prionocidaris baculosa, Echinostrephus molaris, Pseudoboletia indiana, Salmacis bicolor, Stomopneustes variolaris, Toxopneustes pileolus, Clypeaster reticulatus, Metalia spatagus, and Nacospatangus altus. Several novel ecological observations on behavior, diet and morphological variation are also described. These additional occurrences and new observations are attributed to more comprehensive reporting from SCUBA diving as well as the advent of shared resources from social media platforms.